Family resilience of stroke survivors within 6 months after a first-episode stroke: A longitudinal study - Zhang, Wei; Zhou, Wanqiong; Ye, Mingming; Gao, Yitian; Zhou, Lanshu (Frontiers in Psychiatry, 2022)
Context: Family resilience is frequently recognized as a powerful determinant of family adaptation in chronic disease patients; understanding the family resilience of stroke patients and its predictors could help nurses develop interventions to assist patients in maintaining healthy family functioning. Objective: This study aimed to explore the trajectory of family resilience in the six months following stroke onset and examine the predictors of family resilience over time. Methods: A total of 288 first-episode stroke survivors were selected from seven hospitals in China from July 2020 to March 2021. Their family resilience, social support, self-efficacy, and medical coping style were assessed at hospitalization and one month, three months, and six months after stroke onset. The study was performed in accordance with the STROBE guidelines. Results: The mean levels of family resilience were between 95.52±11.10 and 97.68±9.68 within the first 6 months after a first-episode stroke, with a significant increase three months after the onset. Patient self-efficacy, social support, family atmosphere, and caregiver-patient relationship (sibling) were predictors of family resilience at all four time points. Baseline predictors of family resilience at six months included self-efficacy of the patients, subjective support, support utilization, family atmosphere, living district, medical bill payment methods, and caregiver-patient relationship (sibling). Conclusion: Family resilience levels were low in stroke patients six months after the onset, and three months post-stroke onset was a critical period for family resilience of stroke patients. Nurses are recommended to pay particular attention to patients with low self-efficacy, perceived low support, poor utilization of available support, as well as those who are under the care of their siblings, self-pay, or live in a poor family atmosphere. Interventions aimed at improving the self-efficacy of patients and social support are potential approaches to enhance family resilience.